2019
DOI: 10.1177/2319510x19872597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Output Quality and Result Demonstrability on Generation Y’s Behavioural Intention in Adopting Mobile Health Applications

Abstract: The aim of this study is to investigate the relationships between image, output quality, perceived self-efficacy, result demonstrability and Generation Y’s behavioural intention to use mobile health applications. Research data are gathered from a sample of 120 Generation Y participants in Malaysia. Partial least squares structural equation modelling (PLS-SEM) is employed to examine the influences of image, output quality, perceived self-efficacy and result demonstrability on behavioural intention to use mobile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This relationship shows that the tangible aspects (benefits) of mobile apps influence their PU amongst beneficiaries, thereby enhancing the likelihood of app adoption. Previous TAM studies have also found RD's impact on PU (Venkatesh and Davis, 2000; Gow et al. , 2019).…”
Section: Discussionmentioning
confidence: 79%
“…This relationship shows that the tangible aspects (benefits) of mobile apps influence their PU amongst beneficiaries, thereby enhancing the likelihood of app adoption. Previous TAM studies have also found RD's impact on PU (Venkatesh and Davis, 2000; Gow et al. , 2019).…”
Section: Discussionmentioning
confidence: 79%
“…While RD is used in different research studies as an antecedent to PU to explore user acceptance of information technology, this construct has been overlooked in studies on health-related systems such as PHRs. RD was only used in one study of the IT usage of mobile-based health applications, where it was used to examine behavioral intentions to use mobile health applications (Gow et al, 2019). This current study considers the unique addition of RD as a primary construct in a PHR adoption model.…”
Section: Results Demonstrability (Rd)mentioning
confidence: 99%
“…Hubert et al (2019) likewise found a positive relationship between RD and adoption intention for smart homes indicating the relevance of this variable. Additionally, Gow et al (2019) reported a direct positive effect of RD on intention while Yang and Lee (2019) indicated that RD indirectly predicted adoption intention. In essence, when m-commerce has noble features that can be communicated by the SMEs to their colleagues, they will adopt it for their operations.…”
Section: Discussion Of Findingsmentioning
confidence: 99%